Myocardial infarction as a problem of growth control: cell cycle therapy for cardiac myocytes? - Schneider,MD (J Card Fail, 1996)
Pump failure after myocardial infarction ultimately can be ascribed, in large part, to the inability of ventricular muscle to regenerate functional mass through cell proliferation. Recent studies using adenoviral gene transfer have provided direct evidence for the operation of two growth-suppressing pathways in cardiac muscle, via "pocket proteins," including the retinoblastoma gene product, and via a less well understood protein, p300. An understanding of molecular mechanisms that confer a virtually irreversible lock to the proliferative cell cycle in "postmitotic" cardiac muscle, together with improved means for delivery of exogenous genes to the heart, suggests the long-term potential for manipulating cardiac growth to achieve a therapeutic benefit.